2018
DOI: 10.3389/fphys.2018.00755
|View full text |Cite
|
Sign up to set email alerts
|

ER–Mitochondria Microdomains in Cardiac Ischemia–Reperfusion Injury: A Fresh Perspective

Abstract: The mitochondrial and endoplasmic reticulum (ER) homeostasis is pivotal to the maintenance of an array of physiological processes. The physical contact and association between ER and mitochondria, known as the ER–mitochondria microdomains or mitochondria-associated ER membrane (MAM), temporally and spatially regulates the mitochondria/ER structure and function. More evidence suggests a role for MAMs in energy production, cellular contraction and mobility, and normal extracellular signal transmission. In pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 160 publications
(182 reference statements)
3
97
0
Order By: Relevance
“…Moreover, mitochondrial apoptosis has been acknowledged as the primary reason for reperfusion-mediated renal tubular epithelial cell apoptosis [53]. In addition, mitochondrial DNA damage [54], mitochondrial biosynthesis disorder [55], and mitophagy delay [56] have been found to be implicated in mitochondrial dysfunction and renal damage exerted by I/R injury. In the present study, we also found that mitochondria were the potential target of the renal I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mitochondrial apoptosis has been acknowledged as the primary reason for reperfusion-mediated renal tubular epithelial cell apoptosis [53]. In addition, mitochondrial DNA damage [54], mitochondrial biosynthesis disorder [55], and mitophagy delay [56] have been found to be implicated in mitochondrial dysfunction and renal damage exerted by I/R injury. In the present study, we also found that mitochondria were the potential target of the renal I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, mitochondria have been well recognized as major regulators that control heart function and cardiomyocyte viability under physiological and pathological conditions . Structurally, mitochondrial homeostasis is closely regulated by mitochondrial dynamics, including mitochondrial fission, mitochondrial fusion, and mitophagy . Ample evidence has indicated that I/R injury primarily involves multiple factors that converge on provoking the onset of mitochondrial fission .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Structurally, mitochondrial homeostasis is closely regulated by mitochondrial dynamics, including mitochondrial fission, mitochondrial fusion, and mitophagy. 6,7 Ample evidence has indicated that I/R injury primarily involves multiple factors that converge on provoking the onset of mitochondrial fission. 8,9 In contrast to mitochondrial fission, mitochondrial fusion promotes communication between mitochondria, repressing the formation of mitochondrial fragmentation and sustaining mitochondrial genomic homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive accumulation of damaged mitochondria due to mitophagy arrest also promotes the renal dysfunction [9]. Moreover, mitochondrial oxidative stress, mitochondrial calcium imbalance, mitochondrial antioxidant system malfunction, and oxidative phosphorylation cessation [10,11] are the inter-related risk factors for mitochondrial aetiology in diabetic renal disorders. Recently, mitochondrial fragmentation, which primarily results from increased mitochondrial mitotic fission and/or decreased mitochondrial fusion, is found to be correlated with a fall in myocardial function in the setting of hyperglycaemia stress [12].…”
Section: Introductionmentioning
confidence: 99%